Youth entrepreneurship in Germany: Empirical evidence on the how, the why, the how many, the who and the when - Rolf G. Sternberg; David Breitenbach (Economies, 2023)
Youth entrepreneurship is an increasingly prominent aspect of entrepreneurship support policies, but there is surprisingly little relevant research-based empirical evidence. This research gap is particularly noticeable when it comes to the personal and contextual factors that steer young people's decision to start a business. Using statistically representative survey data from the Global Entrepreneurship Monitor for Germany, we apply logit regressions to determine the influence of 10 independent variables on the likelihood of starting a business. We distinguish between 18-24-year-olds and 25-64-year-olds as well as between founders and non-founders. Self-efficacy in entrepreneurial skills, fear of failure and gender are the strongest influencing variables for the person-related factors and knowledge of other founders for the contextual factors. For younger people, the formal level of education and the perception of local entrepreneurial opportunities do not play a role in the decision to start a business, whereas they are very important for older people. Our results suggest that start-up promotion policies should explicitly address the empirically proven factors of youth entrepreneurship instead of a 'one size fits all' policy for new businesses, regardless of the age of the founders.
Keywords: 330; youth entrepreneurship; entrepreneurship; Germany; spatial context; demographics; entrepreneurship policies; Global Entrepreneurship Monitor (GEM)